Logo Therapy Conselling for Gifted Children With Post Trauma Stress Symptoms Due to Rob Disaster and Flood - Rini Sugiarti; Erwin Erlangga (PSIKODIMENSIA, 2018)
The purpose of this study was to help gifted children who experience symptoms of post-traumatic stress so that the potential of gifted children is not lost in vain. In this globalization era, the causes of trauma to individuals are increasing. Individual counseling with logotherapy techniques is considered appropriate to help gifted children who experience symptoms of posttraumatic stress because logotherapy counseling can help gifted children get the meaning of life. This research method was quasi-experimental. The sample in this study were students who experienced posttraumatic stress due to flooding and rob in the Genuk, Sayung, Wringjajar, Morosari and Kalisari regions,Semarang. The total partisipant 10 gifted children. The results of the study showed an increase in the meaning of life of gifted children after being given individual counseling. The hypothesis which states counseling individuals with logotherapy techniques to increase the meaning of life of gifted children who are traumatized by flooding and rob is acceptable.